Enhancements on hybrid coordination function controlled channel access for video transmission in IEEE 802.11E network - Mohammed Al-Maqri, Mohammed Ahmed (2016)
The rapid advancement in wireless technologies and the reduced cost in electronic hardware has stimulated the vast deployment of Wireless Local Area Networks (WLANs) in public and residential places. Nowadays, a wide range of multimedia traffics emerge in WLANs with different Quality of Service (QoS) requirements. In order to support multimedia traffics with stringent requirements, IEEE 802.11e introduced HCF Controlled Channel Access (HCCA). In HCCA, Transmission Opportunity (TXOP) duration is allocated to the QoSenabled Station (QSTA) based on the mean characteristics of its Traffic Stream (TS) described by a TS Specification (TSPEC). Although HCCA operates well for the Constant Bit Rate (CBR) traffics, it is inadequate for Variable Bit Rate (VBR) traffic, where the instantaneous sending rate and the packet size are usually different from its mean values. The aim of this research is to address the deficiency of HCCA in supporting VBR video transmission over wireless networks. Accordingly, a novel polling scheme called Feasible Polling (F-Poll) is proposed to minimize the delay imposed by overpolling stations in the HCCA function. The actual arrival time of the next frame of the uplink TS is obtained and reported to the central scheduler called Hybrid Coordinator (HC). Upon the reception of the data frame at the HC, a decision will be made to poll the corresponding station in the next Service Interval (SI) or not to prevent stations that are not ready to transmit from receiving unnecessary polls. Consequently, the packet access delay and the channel utilization will be enhanced. The TXOP in HCCA scheduler is allocated to the QSTA based on its TSPEC by estimating the amount of data expected to be transmitted by the QSTA during the service interval. Yet, this estimation is not accurate for VBR traffics. Thus, a novel TXOP assignment scheme is proposed which is referred to as Adaptive TXOP Scheme (ATXOP). In this scheme, the TXOP duration is adopted based on the feedback of the actual next frame size reported by QSTAs. So, an accurate TXOP is allocated to the station to ensure that the end-to-end delay is minimized without jeopardizing the channel bandwidth. To leverage the benefit of the ATXOP, a multi-polling scheme has been integrated and named Adaptive Multipolling TXOP Scheme (AMTXOP). Moreover, a new approach incorporating the polling scheme and the TXOP assignment of HCCA scheduler has been presented called Adaptive Feedbackbased HCCA Scheduler (AF-HCCA). The AF-HCCA accommodates to the video applications that show variability in both frame inter-arrival time and frame size, such as H.263 streams. The proposed scheme, accurately assigns TXOP duration time for each traffic stream which is just enough to send their data. Moreover, it only polls QSTAs when needed to minimize the delay and conserve the bandwidth channel. The findings demonstrate that F-Poll is a promising scheme for supporting video streams with a different variability level of frame inter-arrival time while ATXOP scheme and its enhanced version, namely AMTXOP is beneficial for video streams that show variability in packet sizes such as H.264 streams. The integrated scheme shows further improvements for VBR video streams. The results show that F-Poll, ATXOP and AMTXOP schemes outperform the HCCA polling and TXOP assignment schemes in terms of the end-to-end delay and the channel bandwidth utilization while maintaining the system throughput. Moreover, the AF-HCCA shows superior improving in the packet end-to-end delay and remarkably minimize the polling overhead compared to not only the HCCA scheduler, but also to one of the recent enhancement of HCCA scheduler called Enhanced Earliest Due Date (EDD) scheduler.